El principio de concurrencia y su efecto en los procedimientos dinámicos en aras a la normalización de bienes y servicios - Castillo Mera, Eddy Stiven (2025)
This thesis aims to analyze, through a critical legal study, the principle of competition in the National Public Procurement System and its effectiveness in dynamic procedures to determine the relevance of standardizing goods and services required by the State. The objective is to determine the efficiency of the principle of competition and its applicability in the SERCOP, as well as the importance of this principle in dynamic procedures to achieve efficiency in procurement conducted through electronic catalogs and reverse auctions. It also seeks to determine how competition is necessary for public procurement processes to be transparent and efficient, thereby ensuring that the State hires the best suppliers. The possibility of standardizing all goods and services is analyzed, considering the number of processes published and awarded using dynamic procedures such as the electronic catalog and reverse auctions. This is done to verify the regulations regarding public procurement processes, both in dynamic, general, and special procedures. The research employed deductive, analytical legal, deductive legal, and dogmatic methodologies through interviews with legal professionals, allowing for an analysis of the current situation based on the knowledge of experts in administrative matters. In conclusion, the principle of competition is fundamental to an adequate public procurement process. It ensures that all suppliers are aware of the process and equates it with public procurement. Furthermore, it is necessary to standardize as many goods and services as possible, as this reduces public procurement times, saves resources, and protects our country's economy.